أثر المسؤولية الإجتماعية على الأداء المالي في المؤسسة الإقتصادية - دراسة حالة مؤسسة مطاحن بلغيث – مداوروش - سوق أهراس لسنة1 202 - أميرة شخماية; لمياء شخماية (My University, 2021)
This study aims to measure and analys the extent to which economic institutions Are committed to the dimensions and principles of social responsibility and to know the impact of this on their financial performance, based on a questionnaire to reveal the reality of the interest of the institution under study " Baghith Mills " in its social responsibility .then the impact of thèse practicies ,if any,on hier financial performance. Where we dealt with the main independent variable , social responsibility ,which is expressed in the four dimensions of social responsibility :caring for workers protecting customers and product development ,preserving the environment ,and interacting with society.in addition to three secondary dimensions of social responsipility towards : govemment, shareholders and sippliers. The dependent variaple is financial performanace. The study concluded that the "Balghith Mills"corporation is will concerned with its social responsibility to wards: employees , customers , shareholders gouvernement and suppliers . As for its social responsibility towards the environment and socity, it weak which negatively,affecetd ,its fimanancial performance There fore the current stuty recommends the necessity of improving the reputation of "Balghith Mills "Corporation and gaining a good relationship with variois stkehelders .which will improuve its financial performance in the future. ............................................ تهدف هذه الدراسة الى قياس وتحليل مدى التزام المؤسسات الاقتصادية بأبعاد ومبادى المسؤولية الاجتماعية ومعرفة اثر ذلك على ادائها المالي ،وذلك اعتمادا على استبيان للكشف عن واقع اهتمام المؤسسة محل الدراسة "مطاحن بلغيث" بمسؤوليتها الاجتماعية ثم أثر هذه الممارسات ان وجدت على ادائها المالي حيث أناولنا المتغر المستقل الرئيسي المسؤولية الاجتماعية المعبر عنها بالأبعاد الاربعة للمسؤولية الاجتماعية وهي: الاهتمام بالعاملين ،حماية العملاء وأطور المنتج ،المحافظة على البيئة ،التفاعل مع المجتمع . اضافة لثلاثة ابعاد ثانوية هما للمسؤولية الاجتماعية تجاه الحكومة والمسؤولية الاجتماعية تجاه المساهمين ،والموردين .اما المتغير التابع فيتمثل في الاداء المالي. أوصلت الدراسة الى ان مؤسسة "مطاحن بلغيث" تهتم جيدا بمسؤوليتها الاجتماعية :اتجاه العملاء، المساهمين، الحكومة و الدوردين. أما اهتمامها بمسؤوليتها الاجتماعية اتجاه البيئة والمجتمع فكان ضعيف الامر الذي يؤثر سلبا على أدائها المالي . لذا أوصي الدراسة الحالية بضرورة تحسين مؤسسة " مطاحن بلغيث " سمعتها وكسبها علاقة جيدة مع مختلف الاطراف ذات المصالح .الامر الذي سيؤدي الى تحسين أدائها المالي مستقبلا .